MUSIC AND PAIN RELIEF - Tommy Pangandaheng; Tri Nurminingsih Hatala; Fathimah Kelrey (Aloha International Journal of Health Advancement (AIJHA), 2021)
This action aims to know the effect of instrumental music therapy with guided imagery in relieving the intensity of pain in post-operative patients at Rumkit Tk.II Prof. dr. J. A. Latumeten Ambon, Indonesia. The quasi-experimental without control group design and Numerical Rating Score (NRS) were used for measured the level of pain. Twelve (12) participants participated with pretest and post-test. Paired t-test was used to measure the result. Pretest results revealed that majority of the participants were “moderate pain” before receiving the instrumental music therapy with guided imagery. On the same line, there is a significant difference in the level of pain of the participants before and after the intervention. The level of pain of postoperative patients is significantly lower to “mild pain” after their exposure to the instrumental music therapy with guided imagery compared to their level of pain before their reception of the intervention. Instrumental music therapy with guided imagery has a significant positive effect in relieving the intensity of pain of postoperative patients. Keywords: Instrumental music, Guided imagery, Pain